Induction Effect of Fluorine-Grafted Polymer-Based Electrolytes for High-Performance Lithium Metal Batteries - Hu, Haiman; Li, Jiajia; Lin, Fei; Huang, Jiaqi; Zheng, Huaiyang; Zhang, Haitao; Ji, Xiaoyan (Nano-Micro Letters, 2025)
Quasi-solid-state composite electrolytes (QSCEs) show promise for high-performance solid-state batteries, while they still struggle with interfacial stability and cycling performance. Herein, a F-grafted QSCE (F-QSCE) was developed via copolymerizing the F monomers and ionic liquid monomers. The F-QSCE demonstrates better overall performance, such as high ionic conductivity of 1.21 mS cm–1 at 25 °C, wide electrochemical windows of 5.20 V, and stable cycling stability for Li//Li symmetric cells over 4000 h. This is attributed to the significant electronegativity difference between C and F in the fluorinated chain (‒CF2‒CF‒CF3), which causes the electron cloud to shift toward the F atom, surrounding it with a negative charge and producing the inductive effect. Furthermore, the interactions between Li+ and F, TFSI‒, and C are enhanced, reducing ion pair aggregation (Li+‒TFSI‒‒Li+) and promoting Li+ transport. Besides, ‒CF2‒CF‒CF3 decomposes to form LiF preferentially over TFSI–, resulting in better interfacial stability for F-QSCE. This work provides a pathway to enable the development of high-performance Li metal batteries. Highlights: 1 Fluorine-grafted quasi-solid-state composite electrolyte (F-QSCE)@30 exhibits high ionic conductivity of 1.21 mS cm–1 at 25 °C. 2 The inductive effect weakens the coordination between Li+ and TFSI‒, enhancing Li+ transport. 3 LiF in the solid electrolyte interphase of F-QSCE@30 comes from decomposed F segments, not TFSI‒. 4 F-QSCE@30 maintains stability with Li metal for over 4000 h and inhibits dendrite growth.